Characterizing millisecond intermediates in hemoproteins using rapid-freeze-quenched resonance Raman spectroscopy - Matsumura, Hirotoshi (2014)
The combination of rapid-freeze-quenching (RFQ) technique and resonance Raman (RR) spectroscopy represents a unique tool to investigate the nature of short-lived intermediates formed during the enzymatic reaction of metalloproteins. Commercially available equipment allows trapping of intermediates within the millisecond to second timescale for low-temperature RR analysis and direct detection of metal-ligand vibrations and porphyrin skeletal vibrations in hemoproteins. This chapter briefly discusses previous RFQ-RR studies carried-out in our laboratory, and presents as a practical example protocols for the preparation of RFQ samples of the reaction of metmyoglobin with nitric oxide (NO) which requires anaerobic conditions. We also describe important controls and practical procedure for the analysis of these samples by low-temperature RR spectroscopy.